PS-012 Implementation of a support programme for antimicrobial prescription: A 3 month experience. (14th February 2016) - Duarte, H; Costa, G; Diogo, J; Rodrigues, A; Gomes, A; Santos, A; Alcobia, A; Botas, J
Abstract : Background: According to legislation, prescription of carbapenems and quinolones should be reduced by 50% by 2020. The Support Programme for Antimicrobial Prescription aims to survey the incidence rate of multi-drug-resistant microorganisms. Purpose: The objectives were to reduce the consumption of carbapenems by 10% and quinolones by 5% by the end of the year, reducing indicators of infection, defined daily dose (DDD) and DHD (DDD/1000 inhabitants/day) 2015/2014. Material and methods: Longitudinal prospective study. Prescriptions are indicated by the pharmacists who classify requirements as empirical prescriptions, inappropriate prescribing and microbiologically documented prescriptions. If necessary, the prescriptions are changed by infectiologists. We compared data from January to August 2015 with the same period in 2014. Patients were admitted between June and August 2015. Results: The variation between the DDD was 88.8% for carbapenems, and 94.7% (intravenous) and 79.3% (oral) for quinolones. The carbapenems decreased by 11.2% in total DDD. The intravenous quinolones decreased by 5.3% and the oral reduction was 15.6%. The DHD values were calculated and had the same trend of decreasing consumption. During the study period, 263 patients were identified. We analysed 183 carbapenem and 81 quinolone prescriptions. 152 were men and mean age was 68.8 ± 15.9 years. The most common site of infection was urinary tract infection. Intervention occurred in 92 empirical prescriptions, 52 inappropriate prescribing, 79 documented and 36 according to the protocol. The prescription was changed in 59 patients. Duration of therapy was 7.3 days for patients without an intervention and 4.9 days with an intervention. We found that in 116 microbial isolates, 55 were multi-resistant. Of the monitored patients, 199 were discharged, 32 died and 32 remain hospitalised. Conclusion: The proposed objective was attained by August. The national target to reduce the DHD was also fulfilled. There has been investment in surveillance of surgical prophylaxis protocols, as reflected in the decreasing consumption of quinolones. References and/or Acknowledgements: Despacho No 1400 A/2015 10 Fevereiro Diário República 28 (2015) No conflict of interest.